Lysis of the long process of the incus secondary to Vibrant SounBridge® middle ear implants, treated with hydroxyapatite bone cement. Issue 6 (December 2019) - Pitiot, Vincent; Hermann, Ruben; Coudert, Aurélie; Truy, Eric
Abstract: We report two patients presenting with delayed complicationsafter Vibrant SounBridge® middle ear implant surgery: in both cases, a revision surgery was performed and lysis of the long process of the incus was highlighted. A re-assembly of the clip around the remaining long process of the incus was performed, associated with hydroxyapatite bone cement application, on the clip and the incudo-stapedial joint. Both patients had a satisfying result, with a mean follow up of 12 months.